A study of impact of cement exposure to health of construction workers / Ros Aini Razali - Razali, Ros Aini (Faculty Architecture, Planninng and Surveying, 2015)
Rosenthal (2007), in booming economies from Asia to Eastern Europe, cement is literally the glue of progress. A binding agent that holds the other ingredients that together make concrete, cement is a crucial component in buildings and roads. Cement is a basic problem such as the chemical reaction that can creates it releases large amounts of carbon dioxide which can cause a pollution. Despite the pollution, people may not know from cement raw materials can affect to one’s health and bodily harm. This study will provide the level of workers awareness of working with cement that can adverse to their health and bodily harm in future. They may say experience taught them to be extra cautious in future to prevent and dangers or mistakes. However, at the end of the least of knowledge on the harm of cement can cause play an important role. From that, any incidents or hazardous can be void or lessen in construction site area. Though the workers are not aware of these dangers coming from cement exposure they should be taught and guided on how to handle cement with right and safe. From a rough observation cement raw materials may seem fine and would not give such a huge impact to the person handling it. Unfortunately, it does not what it seems to be as it will affect to the person where it cannot be seen with a proper observation. This should be given a lot of concern from the responsible employer for the worker welfare. Cement is not only harmful to the environment where it came from the cement dust that spread in the air. But, it also have an after effect once it has completely hardened and become a concrete. So, the beginning of these harm is come from the cement that people do not aware and this is getting a lot of concern from the industry sector. So, a proper education regarding cement hazard should be taken for the people that handling it and people that surrounded by it.